PROBLEMS AND CHALLENGES IN MEDICAL TRANSLATION AND THEIR CONSEQUENCES - Ibodullaeva Azizabonu Kuvandik qizi (Modern American Journals, 2025)
In today’s globalized world, medical knowledge circulates rapidly across borders, reaching physicians, researchers, policymakers, and patients in many different countries. Accurate medical translation is therefore of vital importance. It ensures that clinical guidelines, pharmaceutical instructions, research articles, and patient records are communicated clearly and reliably across languages. However, the field of medical translation presents a wide range of difficulties. The consequences of mistranslation in this area are often severe, as they may directly affect patient safety, public health, and the advancement of medical science.This article explores the main problems and challenges in medical translation, including linguistic, cultural, and technical barriers, and examines the potential consequences of errors or inadequacies in this process. Problems in medical translation include complex jargon, lack of direct equivalents, cultural variations, regulatory differences, and the high stakes of accuracy, leading to severe consequences such as misdiagnosis, incorrect treatment, legal issues, lack of informed consent, and compromised patient privacy. Overcoming these challenges requires working with specialized translators, using glossaries, ensuring cultural competence, adhering to strict confidentiality, and providing training for healthcare staff.
Keywords: misdiagnosis, incorrect treatment, legal issues, lack of informed consent, and compromised patient privacy